miR-524-5p of the primate-specific C19MC miRNA cluster targets TP53IPN1- and EMT-associated genes to regulate cellular reprogramming - Nguyen, Phan Nguyen Nhi; Choo, Kong Bung; Huang, Chiu-Jung; Sugii, Shigeki; Cheong, Soon Keng; Kamarul, Tunku (Stem cell research & therapy, 2017)
Background Introduction of the transcription factors Oct4, Sox2, Klf4, and c-Myc (OSKM) is able to ‘reprogram’ somatic cells to become induced pluripotent stem cells (iPSCs). Several microRNAs (miRNAs) are known to enhance reprogramming efficiency when co-expressed with the OSKM factors. The primate-specific chromosome 19 miRNA cluster (C19MC) is essential in primate reproduction, development, and differentiation. miR-524-5p, a C19MC member, is highly homologous to the reprogramming miR-520d-5p; we also reported that miR-524-5p was expressed in iPSCs but not mesenchymal stem cells (MSCs). This study aimed to elucidate possible contributions of miR-524-5p to the reprogramming process. Methods A miR-524-5p precursor was introduced into human fibroblast HFF-1 in the presence of OSKM, and the relative number of embryonic stem cell (ESC)-like colonies that stained positively with alkaline phosphatase (AP) and Nanog were quantified to determine reprogramming efficiency. A miR-524-5p mimic was transfected to MSCs to investigate the effects of miR-524-5p on TP53INP1, ZEB2, and SMAD4 expression by real-time polymerase chain reaction (PCR) and Western blot. Direct gene targeting was confirmed by luciferase activity. A phylogenetic tree of TP53INP1 was constructed by the Clustal method. Contribution of miR-524-5p to cell proliferation and apoptosis was examined by cell counts, BrdU, MTT, and cell death assays, and pluripotency gene expression by real-time PCR. Results Co-expressing the miR-524 precursor with OSKM resulted in a two-fold significant increase in the number of AP- and Nanog-positive ESC-like colonies, indicating a role for miR-524-5p in reprogramming. The putative target, TP53INP1, showed an inverse expression relationship with miR-524-5p; direct TP53INP1 targeting was confirmed in luciferase assays. miR-524-5p-induced TP53INP1 downregulation enhanced cell proliferation, suppressed apoptosis, and upregulated the expression of pluripotency genes, all of which are critical early events of the reprogramming process. Interestingly, the TP53INP1 gene may have co-evolved late with the primate-specific miR-524-5p. miR-524-5p also promoted mesenchymal-to-epithelial transition (MET), a required initial event of reprogramming, by directly targeting the epithelial-to-mesenchymal transition (EMT)-related genes, ZEB2 and SMAD4. Conclusions Via targeting TP53INP1, ZEB2, and SMAD4, miR-524-5p contributes to the early stage of inducing pluripotency by promoting cell proliferation, inhibiting apoptosis, upregulating expression of pluripotency genes, and enhancing MET. Other C19MC miRNAs may have similar reprogramming functions.